Examining the impact of parental education and socio-demographic factors on career aspirations in adolescent students in Delhi NCR, India: A cross-sectional study - Praveen Kumar Pandey; Prashant Kumar Pandey; Samriti Mahajan; Nandini Srivastava; Mohd Asif Shah (Cogent Business & Management, 2024)
The purpose of this study was to examine the factors that influence career aspirations in students, including the role of university, gender, and parental education. The research methodology involved analyzing the attitudes of students at four universities in India using a closed-ended questionnaire and factor analysis, MANOVA, and Structural-Equation-Modeling (SEM) analysis. The results showed significant differences in the attitudes of students at private and government universities, and a significant effect of parental education, but no significant impact of gender. However, the study had a limitation of data collected from only four specific universities and may not be representative of the entire national university population. The findings have practical implications for universities to improve the positive attitudes of their students and increase their motivation levels. This study is original in its focus on the impact of parental education and socio-demographic factors on career aspirations in adolescent students in Delhi NCR, India, the first of its kind in this population in the Delhi NCR region of India.
Keywords: J13; J24; 650; attitude; career aspirations; gender; parental education; socio-demographic factors; Structural-Equation-Modeling (SEM)